Research trend on ethnomathematics from 2012 to 2022: A bibliometric analysis - Rusli, Rusli; Safaah, Tusana Nurul (Universitas Islam Negeri Raden Intan Lampung, 2023)
Ethnomathematics integrates mathematical concepts with cultural practices, making mathematics education more relevant and engaging. Given the abstract nature of mathematics, this approach plays a crucial role in enhancing student interest and comprehension. This study aims to analyze global research trends in ethnomathematics from 2012 to 2022 by identifying key themes, influential authors, and research patterns. A bibliometric analysis was conducted on 994 documents retrieved from Google Scholar, utilizing Publish or Perish, Microsoft Excel, and VOSviewer for data processing and visualization. The findings reveal a steady increase in ethnomathematics publications, with journals being the predominant dissemination medium. Four primary research themes emerged: educational practices, integration into mathematics learning, development of teaching materials, and pedagogical approaches. The study concludes that ethnomathematics research continues to expand, reflecting a growing academic interest in culturally responsive mathematics education. The implications of this study emphasize the need for sustained research efforts to integrate cultural perspectives into mathematics education, fostering greater student engagement and promoting educational equity.